Astrocyte lipid metabolism is critical for synapse development and function in vivo. Issue 4 (7th February 2017) - van Deijk, Anne‐Lieke F.; Camargo, Nutabi; Timmerman, Jaap; Heistek, Tim; Brouwers, Jos F.; Mogavero, Floriana; Mansvelder, Huibert D.; Smit, August B.; Verheijen, Mark H.G.
Abstract: The brain is considered to be autonomous in lipid synthesis with astrocytes producing lipids far more efficiently than neurons. Accordingly, it is generally assumed that astrocyte‐derived lipids are taken up by neurons to support synapse formation and function. Initial confirmation of this assumption has been obtained in cell cultures, but whether astrocyte‐derived lipids support synapses in vivo is not known. Here, we address this issue and determined the role of astrocyte lipid metabolism in hippocampal synapse formation and function in vivo. Hippocampal protein expression for the sterol regulatory element‐binding protein (SREBP) and its target gene fatty acid synthase (Fasn) was found in astrocytes but not in neurons. Diminishing SREBP activity in astrocytes using mice in which the SREBP cleavage‐activating protein (SCAP) was deleted from GFAP‐expressing cells resulted in decreased cholesterol and phospholipid secretion by astrocytes. Interestingly, SCAP mutant mice showed more immature synapses, lower presynaptic protein SNAP‐25 levels as well as reduced numbers of synaptic vesicles, indicating impaired development of the presynaptic terminal. Accordingly, hippocampal short‐term and long‐term synaptic plasticity were defective in mutant mice. These findings establish a critical role for astrocyte lipid metabolism in presynaptic terminal development and function in vivo. GLIA 2017;65:670–682 Main Points: Diminishing lipid biosynthesis in astrocytes leads to presynaptic terminal abnormalities and deficits in short‐ and long‐term synaptic plasticity. A critical role for astrocyte lipids in synapse development and function in vivo is established.